Analisis Dan Perancangan Sistem Informasi Manajemen Anggaran Pada Badan Perencanaan Pembangunan Daerah Provinsi Jambi - Suherdiansyah, Febri; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2020)
BAPPEDA has the task of assisting the Governor in carrying out some regional government affairs in the area of regional development planning based on the applicable laws and regulations. a) The Jambi Provincial Regional Development Planning Agency carries out functions: formulating technical policies for regional development planning; b) coordinating the preparation of regional development planning; c) fostering the implementation of tasks in the area of regional development planning; d) implementation of regional development control and evaluation; and e) other functions performed by the Governor in accordance with their duties and functions. In carrying out its functions, BAPPEDA is inseparable from the problems, namely a) Inconsistent planning and budgeting, among planning documents such as the absence of programs in the Jambi Provincial Medium-Term Development Plan (RPJMD). b) Does not match program name in Jambi Province RPJMD. c) There are no activities in the Strategic Plan (RENSTRA). d) Does not match the target activities that have been set in the Strategic Plan. From these problems the writer tries to design a budget management information system using the Unified Modeling Language (UML) system modeling and the results are in the form of a prototype system design. This research resulted in a prototype of the Budget Management Information System design at Badan Perencanaan Pembangunan Daerah (BAPPEDA) Jambi Provincial. With the design of the Budget Management Information System it is expected to be the basis for solving problems that occur at Badan Perencanaan Pembangunan Daerah (BAPPEDA) Jambi Provincial. In this research, it is expected that BAPPEDA can measure the realization of outputs of activities against planned plans and can monitor the achievement of activity outputs.